The effect of pre-harvest application of priming agents on quality attributes and phytochemical properties of strawberry - Assiotis, Andreas (My University, 2025)
Strawberry (Fragaria x ananassa) can be cultivated under a wide range of ecological conditions and its fruit is highly appreciated due to its attractive flavour, juicy texture, bright red color and sweetness. In addition, strawberry is a rich source of vitamins and bioactive compounds. Plant priming is a significant technique for sustainable agriculture, as it can decrease the necessity for chemical fertilizers and pesticides, enhance crop harvest and quality, and conserve natural resources. The application of priming agents is additionally a promising strategy for improving the nutritional content and overall quality of fruits. Thus, the aim of this study was to evaluate the effect of an array of compounds (melatonin (Mel), sodium alginate (NaA), a combination of melatonin and sodium alginate, and putrescine dihydrochloride(Put)) on the quality characteristics and secondary metabolites of an early-harvested strawberry variety. To this aim, fruit were sprayed directly at three developmental stages: large green (LG), small white (SW), and large white (LW). Fruits sprayed with water were used as control. Putrescine-treated strawberries were characterized by higher firmness values compared to those treated with melatonin and water. No differences in soluble solids content (SSC) were detected. Among sugars, glucose and fructose remained unaffected irrespective of the treatment applied. The total flavonoids content showed higher concentration on fruits treated with Mel-NaA and Put, as well as, in NaA-treated. No striking differences in the contents of total phenolics, reduced ascorbic acid, and total anthocyanins were detected among treatments applied.
Keywords: Fragaria x ananassa; strawberry; priming agents; melatonin; sodium alginate; putrescine; phytochemicals; colour; anthocyanin; aroma; φραουλα; Fragaria x ananassa; φαινόλες; παράγοντες ενεργοποίησης; μελατονίνη; αλγινικό νάτριο; διυδροχλωρικής πουτρεσκίνης